Interactive E-Modules with Hologram and Text-to-Speech: An Innovative Media for Teaching the Human Excretory System - Nukhbatul Bidayati Haka; Yuni Fitriani; Meita Dwi Solviana; Ismi Rakhmawati (Al Jahiz, 2025)
This research aimed to develop an interactive e-module with hologram and text-to-speech technologies for teaching junior high school science, specifically the human excretory system, in grade VIII. Using an R&D approach based on the Borg and Gall model up to the 7th stage (problem identification, data collection, product design, design validation, product trials, and revision), the e-module was validated by six experts. The study involved students from SMPN 1 Bumi Ratu Nuban Lampung Tengah, including 10 students for small group trials and 30 students for field trials. The results showed that the e-module, with 82% validation from media experts, 92% from content experts, and 88% from language experts, was highly valid. Student trials also indicated that the e-module on animal tissue material was engaging, with a 78% rating in small group trials and 80% in field trials. This study offers a valuable contribution to enhancing education through innovative, technology-based learning media.